Research on house prices, accessibility and socio-economic neighborhood attributes in southern Sweden - Zoltan Kettinger; David Emanuel Andersson (European Regional Science Association (ERSA), 2012)
According to social scientists such as Richard Florida and Ronald Inglehart, the structural changes that accompany post-industrialization not only change the industrial and occupational structures of post-industrial regions. They also affect the value structure so that creativity, quality of life and tolerance are valued more than money and material possessions. According to economic theory, the subjective preferences of consumers should determine the willingness to pay for various goods. One of the most important goods that individuals consume is housing, and hence changes to the value structure should influence the willingness to pay for housing attributes to the extent that such attributes reflect relevant values. Using a hedonic approach, implicit prices are estimated for relevant neighborhood attributes in the Malmö metropolitan area in southern Sweden. The tested hypothesis is that "post-industrial preferences" imply a greater valuation of creative-class concentration, ethnic diversity, and aesthetic satisfaction as desired neighborhood attributes. Conversely, traditional neighborhood attributes such as mean income and the percentage of low-income immigrants should be less influential as price determinants in post-industrial "creative" cities. Using both log-linear and Box-Cox transformed functional forms, hedonic price functions are estimated for the greater Malmö region, which currently encompasses the western half of the province of Scania.
Keywords: 330; creative class; hedonic prices; postindustrialization; neighborhood attributes